Fertility restoration, combining ability effects and heterosis in sunflower (Helianthus annuus L.) using different CMS sources: FERTILITY RESTORATION, COMBINING ABILITY EFFECTS AND HETEROSIS IN SUNFLOWER - C R MEENA; H P MEENA; B SINHA (Journal of Oilseeds Research, 2013)
Combining ability studies were made in sunflower (Helianthus annuus L.) using line x tester analysis with two diverse CMS lines PET-1 and ARG-1 and 12 testers. Analysis of variance revealed significant differences among the genotypes i.e., parents and hybrids. Non-additive type of gene action was found important for expression of all the charactersstudied. Studies on identification of effective restorer linesrevealed that out of 12 inbreds,fourturned out to be restorers for both PET-1 and ARG-1, while eight behaved as maintainers. Among the lines, PET-1 was found to be good general combiner forseed yield and oil content. Testers HAM-161, RHA-273 and HAM-174 have also exhibited desirable general combining ability effect for seed yield and several other characters. The cross combination ARG-1 x RHA-273 and ARG-1 x RHA-274 were found to be promising for most ofthe characterssuch as seed yield, plant height, number of leaves, capitulum diameter, stem girth and 100-seed weight. Besides PET-1 source, other source viz., ARG-1 used in the present investigation was equally efficient in expressing their fullest potential of yield and yield contributing characters. Most of the crosses involving high x low general combining parents, exhibited high sca effects for various traits.